Synthesis and Characterization of a New Series of [1, 3]-Oxazepine Compounds from Heterocyclic Schiff Bases - Roshna B. Nadr; Bana S. Abdulrahman (Zanco Journal of Pure and Applied Sciences, 2023)
In this study a new Series of aromatic heterocyclic [1, 3]-oxazepine have been synthesized by two steps. The first-step included synthesis of imine derivatives (1–7) using glacial acetic acid as a catalyst in the condensation reaction of 4-(6-methylbenzothiazol-2-yl)aniline with various substituted aromatic aldehydes. While in a second step, a series of seven-membered heterocyclic ring derivatives (8-14) obtained from Schiff base derivatives with phathalic anhydride in dry benzene. A variety of experimental techniques were used to characterize the new derivatives, including melting point, FT-IR, 1H-NMR, and 13C-NMR. Finally, the synthesized compounds were screened against two types of bacteria both Staphylococcus aureus Gram (+ve) and Escherichia coli Gram (-ve) microorganisms. The results revealed that slightly active to good active against both types of test organisms of bacteria.